Operative complications and results of the SPAR procedure for stress urinary incontinence - Orešković, Slavko (Array, 2009)
Abstract: The aim of this study was to determine the efficacy and operative complications of the suprapubic arc (SPARC) procedure in stress incontinent women with and without previous anti-incontinence surgery. One-hundred and twenty-one patients with stress urinary incontinence (SUI) were treated with SPARC for correction of urethral hypermobility (N=65) and intrinsic sphincter deficiency (N=56) between August 2002 and February 2007. The long-term surgical results, operative complications (bladder injury, retropubic hematoma, de novo urgency and urinary infection) and patients’ satisfaction were assessed. The overall complication rate was 9.9% (12/121). The perioperative complication rate was 1.7% including 2 urinary bladder injuries. Significant difference in the overall complications rate was detected between women with and without previous surgery (23/45, 51.1% vs. 6/108, 5.5%, c2=49.89, P<0.001). The overall postoperative complication rate was 8.3% (10/121) including 4 de novo urgencies, 4 urinary infections and 2 retropubic hematomas. There were 3 patients with postoperative urinary retention managed conservatively, without voiding difficulties on control visits. The objective cure rate after the follow-up was 86.8% (105/121). In patients with SUI and without preceding vaginal operations SPARC is a good method with low incidence of perioperative complications, promising long-term results and high patient satisfaction